Pengaruh Model Pembelajaran Problem Based Learning Terhadap Karakter Mandiri Siswa Kelas 4 SDN 04 Kedoya Utara - Falikah Rojali; Fitria Rosmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of the Problem-Based Learning (PBL) instructional model on the independent character of fourth-grade students at SDN 04 Kedoya Utara, West Jakarta. The background of this study arises from the low level of student independence, as students still tend to rely on teachers in completing tasks. This research employed a quantitative method with a quasi-experimental design using the Posttest Only Control Design. The sample consisted of two classes, namely the experimental class and the control class, with a total of 64 students. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, and then analyzed using an Independent Samples T-Test through SPSS version 22. The results indicate a significant effect of the Problem-Based Learning model on students’ independent character, with a significance value of 0.001 < 0.05. This finding demonstrates that the implementation of PBL can enhance students’ sense of responsibility, discipline, curiosity, and self-confidence in learning. Keywords: Problem Based Learning, Independent Character, Elementary School Students